La regulación de los precedentes administrativos en el ordenamiento jurídico peruano - Cairampoma Arroyo, Alberto (2014)
The importance of providing equal treatment to citizens, and of the predictability of public administration in resolving their disputes or requests is undeniable. In this context, the administrative precedent is an important tool to achieve the aforementioned objectives, allowing the performance of Public Administrations to provide legal certainty and avoid arbitrary situations.